Analisis Sentiment Pengguna X Terhadap Hilirisasi Kemenyan Menggunakan Algoritma Naïve Bayes - Utama, Farrel Rizki; Suaidah, Suaidah (Forum Kerjasama Pendidikan Tinggi, 2025)
The issue of frankincense downstreaming in Indonesia is a significant concern because it has the potential to increase the economic value of local commodities and the welfare of the community, especially farmers. However, public perception of this downstreaming policy is still diverse and has not been widely analyzed scientifically, especially on social media. Therefore, this study aims to analyze the sentiment of social media users X towards the issue of frankincense downstreaming using the Naïve Bayes algorithm. The research data was obtained through a crawling process using the Twitter API with the keywords